Foundations of Basilian Monasteries in the Grand Duchy of Lithuania in the 17th Century - Wereda, Dorota (History / Istorija, 2025)
A breakthrough event in the history of the Eastern Churches in the Polish-Lithuanian Commonwealth was the synod held in Brest in 1596, as a result of which a religious community was established that recognised the authority of the papacy. The Basilian Order, reformed in 1617 and establishing the Lithuanian Basilian Province of the Holy Trinity, was able to be a helpful environment in implementing the idea. In this article, I present the places and circumstances of the foundation of 37 Basilian monasteries in the Grand Duchy of Lithuania in the 17th century and their founders. I analyse the political environments of the founders and the influence of the policy of the rulers of the Polish-Lithuanian Commonwealth on the dynamics of the foundations. I present the territorial conditions of monastic foundations. The results of the analyses showed the decisive role of the religious policy implemented by the monarchs in the 17th century.